المصطلح اللّسانيّ و دوْره في تسْهيل تعلّم اللّسانيّات - موساوي, عبد العالي (University of El-oued, 2017)
شهدت ستّينات القرن الماضي ولادة اتّجاه جديد في حقل الدّراسات اللّغويّة العربيّة , استحقّ أن يُميّز باسم خاصّ و هو"اللّسانيات" , فاقتضى الأمر بيان حدود هذا العلم وإنشاء مصطلحات خاصّة به تساعد على ضبط مفاهيمه وتصنيف ظواهره ,ليسهل بذلك تعليمه وتعلّمه. ذلك أنّ المصطلح اللّساني أرقى ما تصل إليه اللّغة في تشكيل مفاتيح علومها والتّعبير عن مفاهيمها بطرق تجعل التّفاهم ممكنا, والتّواصل سهلا.إلا أنّ الاضطراب الواقع حوله في عدم ضبطه في التّعليم العالي حاليّا, أو الكتابات اللّسانيّة العربيّة. حوّله عقبة كؤودا لتلقّي اللّسانيات.و ذلك راجع إلى تعدديّة المناهج المتّبعة في صوغه. وأيّ اضطراب أو خلل في إطلاق المصطلحات أو عدم مراعاة مفاهيما ومجموعتها وأنظمتها، أو عدم التّنسيق الكامل المسبق في وضع المصطلحات يؤدّي إلى الخلط، و صعوبة الدّرس اللّسانيّ بكل فروعه المعرفيّة و المنهجيّة، التي يتلّقاها الطّالب الجامعي. The sixties of the last century witnessed the birth of a new trend in the field of Arabic language studies, which deserved to be distinguished by a special name, "Linguistics", which required the definition of the boundaries of this science and the establishment of specific terms that help to control its concepts and classification of phenomena, . The linguistic term is the finest language in the formation of the keys to science and expression of concepts in ways that make understanding possible, and communication is easy. However, the turmoil surrounding him in the lack of control in higher education now, or the writings of the Arabic language. Around which he found a major obstacle to receiving linguistics. This was due to the plurality of the methods used in its formulation. Any confusion or malfunction in the launch of terminology or lack of respect for concepts, group and systems, or lack of full coordination in the pre-development of terminology leads to confusion, and the difficulty of linguistic lesson in all branches of knowledge and methodology, received by university students
مقال. Ex Professo. مج2. ع.1. جامعة الوادي
Keywords: المصطلح اللّساني، تعليميّة المصطلح, اللّسانيات; The linguistic term, Linguistics, terminology